Posterior cruciate ligament reconstruction in an older adult patient with multiligamentary knee injury - Guillén Morales, Julio César (2022)
The multiligamentary knee injuries are complex high-energy trauma with a devastating prognosis. This injury is rare in older adults whose treatment is controversial. Surgical treatment in older adults may present similar functional results as in younger patients. Present the case of a 75-year-old woman with total posterior cruciate ligament (PCL) rupture, total medial collateral ligament (MCL) rupture and partial anterior cruciate ligament (ACL) rupture with <50% thickness in the right knee. The surgery performed was an arthroscopic reconstruction of the PCL with a posterior tibial allograft and repair of the superficial MCL. The preoperative KOS-ADL score was 42.9% and the postoperative was 81.4% at 18 months of follow-up. The reconstructive surgery in multiligamentary knee injuries is clinically feasible in older adult patients with an acceptable and satisfactory clinical outcome.